AIM2 promotes excitatory glutamate receptor expression by inhibiting STING and contributes to bone cancer pain in male mice - Linhan Wang; Xueqin Xu; Shanchun Su; Biyun Li; Kunyu Zhang; Xiuqin Yu; Yangqiao Xiao; Shuangshuang Lu; Zihao Lu; Yanqiong Wu; Changbin Ke (Scientific Reports)
Abstract Bone cancer pain (BCP) is a common clinical problem in cancer patients. The plasticity of excitatory neurons within the spinal dorsal horn plays a significant role in the development of BCP. This study explored the roles of absent in melanoma 2 (AIM2) and stimulator of interferon gene (STING) in BCP using male C57BL/6J mice. Cancers cells were cultured and implanted into the tibia to induce pain-like behavior. AIM2-RNAi lentivirus was injected into spinal dorsal horn or STING agonist was injected intraperitoneally. The protein expressions and localization were evaluated by qRT-PCR and WB or IF, respectively. The mechanical pain threshold was measured using the von Frey test. Immunofluorescence showed that AIM2 and STING were co-localized in spinal cord neurons, and AIM2 was expressed in the presynaptic membrane. qRT-PCR and western blotting showed that AIM2 expression was increased, and STING expression was decreased in cancer implanted mice. Inhibition of AIM2 enhanced the expression of STING and reduced the expression of GluN1, and attenuated mechanical allodynia. After injecting of STING agonist, the mechanical pain threshold was increased and the expression of GluN1 was decreased. These results emphasizes the involvement of AIM2 in BCP development by downregulating STING expression and increasing GluN1 expression.